Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil - Souza, Maysa F.v.r.; Ferreira, Rodrigo L. (Zootaxa, 2016)
Two new species of troglobiotic Brazilian palpigrades are described: Eukoenenia jequitinhonha sp. n., found in Lapa do Córrego do Vieira cave (Caraí, Minas Gerais) and E. cavatica sp. n., found in Cazanga cave (Arcos, Minas Gerais). The importance of documenting the occurrence of troglobiotic species, even if they are represented by only a single specimen, is discussed.